Neither cloud cover nor low solar loads are associated with fast marathon performance - Ely, M. R.; Cheuvront, S. N.; Montain, S. J. (Medicine & Science in Sports & Exercise, 2007)
There exists a popular notion that cloud cover and/or low solar radiation increase the likelihood of running a fast marathon. This information can be found in anecdotal reports, authoritative reference books for runners, and scientific publications alike, but it lacks a comprehensive review.